A method of repairing a graphite susceptor surface SiC coating

CN118619713BActive Publication Date: 2026-10-30ZHEJIANG LIUFANG CARBON TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410759040.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2026-10-30
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

但存在的问题是,大量树脂(包括黏结剂、胶结剂和胶黏剂)热处理过程中会因分解产生泡孔和裂纹,以致纯硅焊接后,修补处难以形成连续相的SiC,当未反应的残余硅被去除后,留下泡孔和裂纹

Benefits of technology

[0038](1)本发明首先采用热解后残余碳含量高的聚合物与碳化硅填料填补石墨基座表面SiC涂层的受损处,加热使所述聚合物碳化形成多孔结构,由于碳化硅的支撑作用,大大减小了所述聚合物在热解过程中的变形、发泡或收缩,同时避免引入其他杂质;然后,在多孔结构表面涂覆硅单质与聚碳硅烷形成的浆料,加热至硅单质熔点以上,一方面硅单质熔渗进入多孔碳结构发生反应生成SiC,另一方面聚碳硅烷熔渗进入多孔碳结构热解形成SiC,甚至当石墨裸露时熔渗进入石墨内部热解为SiC,并且由于聚碳硅烷的存在,将液态硅的熔渗区域限制在多孔结构区域附近,避免了液态单质硅由于粘度低过度流动而造成未充分参与反应无法形成连续的SiC防护层的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118619713B_ABST
    Figure CN118619713B_ABST
Patent Text Reader

Abstract

The application provides a repairing method for a graphite base surface SiC coating. First, a compound of a polymer with high residual carbon content after pyrolysis and silicon carbide fillers is used to fill the damaged part of the graphite base surface SiC coating, and the polymer is carbonized to form a porous structure through heat treatment; then, a slurry formed by silicon and polycarbosilane is coated on the surface of the carbonized polymer and silicon carbide fillers, and a melting infiltration treatment is performed above the melting point of silicon. By using the method, a high-density SiC repair layer with high bonding force with the surrounding structure can be formed at the damaged part, and the service life of the graphite base can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of graphite materials and surface protection technology, specifically relating to a method for repairing SiC coatings on the surface of a graphite substrate. Background Technology

[0002] Metal-organic chemical vapor deposition (MOCVD) is a technique that utilizes the thermal decomposition of organometallic compounds to epitaxially grow thin single-crystal materials of various group III-V or II-VI compounds and their multi-component solid solutions, including GaAs, AlAs, AlGaAs, InP, InAlAs, AlN, GaN, and GaP. Using MOCVD technology, these nanometer-thick single-crystal materials can be deposited with high precision and controllability, forming materials with specific optical, electrical, or magnetic properties. Therefore, it is widely used in the fabrication of various thin-film materials, including semiconductor devices, optical devices, gas-sensitive elements, superconducting thin films, ferroelectric / ferromagnetic materials, and dielectric thin films.

[0003] The basic components of an MOCVD (Metal-Oxide-Chemical Vapor Deposition) system include: a gas source transport system, a reaction chamber, a tail gas transport system, and a control and in-situ monitoring system. The reaction chamber is the core of the MOCVD growth system, comprising a quartz or stainless steel cavity, a support base, a substrate heater, pressure and temperature sensors, and a cooling system. It plays a crucial role in the thickness, uniformity, quality, and impurity concentration of the epitaxial layer. The raw materials or products used in MOCVD are generally corrosive, the process temperatures are high, and the requirements for gas flow, temperature uniformity, and contaminant control are extremely stringent. Therefore, the substrate needs to be placed on a clean, contamination-free base capable of supporting and heating the single-crystal substrate. Among various material selections, graphite stands out due to its excellent comprehensive properties, including high temperature resistance (melting point 3850±50℃, boiling point 4250℃, stable in an inert atmosphere), high thermal conductivity (range 120-200 W / (m·K), good thermal conductivity gives graphite uniform heat transfer), and a low coefficient of thermal expansion (approximately 7.1×10⁻⁶). -6 ~1.1×10 -5Graphite is the preferred substrate due to its high temperature resistance (around -℃), ability to withstand rapid temperature changes without cracking, ease of processing (convenient cutting and polishing, and the ability to be processed into high-precision substrates of various shapes), and relatively low price. However, graphite has low hardness and poor interlayer bonding, making it susceptible to wear and easy for graphite powder to fall off. Graphite is also susceptible to oxidation and corrosion, easily corroded by carrier gas or gas source during MOCVD processes. Furthermore, graphite releases gases at high temperatures, which can contaminate the epitaxial growth environment and reduce film quality. Therefore, graphite cannot be directly used in MOCVD reaction chambers; it must be coated with a protective coating to effectively isolate it from corrosive gases during the MOCVD process and impart corrosion and wear resistance to the graphite substrate, thereby improving the quality of crystal epitaxy and the service life of the graphite substrate.

[0004] Silicon carbide (SiC) ceramics possess excellent properties such as high strength, high thermal conductivity, corrosion resistance, and high temperature resistance, making them one of the ideal high-safety materials for extreme environments such as high temperature, strong neutron irradiation, high-speed friction, and strong corrosion. There are many SiC crystal forms, among which β-SiC can be used as a thin film and coating material to protect materials used in high-temperature, high-wear, and highly corrosive working environments. Furthermore, the coefficient of thermal expansion and thermal conductivity of β-SiC are very close to those of graphite, making it the preferred material for coating the surface of graphite substrates in wafer epitaxy equipment. This can solve the failure of graphite substrates caused by high-temperature oxidation and corrosion during service, thereby improving the quality of crystal epitaxy and the service life of graphite substrates. In the 1950s and 1960s, Rustum Roy and others at Bell Labs pioneered the deposition of SiC coatings on graphite surfaces using chemical vapor deposition (CVD). In the decades that followed, the preparation technology of CVD silicon carbide coatings has continuously progressed and achieved breakthroughs, expanding from laboratory research to industrial applications.

[0005] Although SiC coatings have significantly improved the lifespan of graphite substrates, in practical use, SiC coatings are susceptible to damage (including wafer impact and transport breakage), resulting in cracks, impact points, scratches, breaks, chipping, peeling, and corrosion pits. This can even expose the graphite substrate, where corrosive gases from the MOCVD process can then erode the damaged areas, causing them to gradually enlarge and ultimately rendering the substrate unusable. Repairing damaged SiC coatings to extend the lifespan of graphite substrates remains a key research area in the industry.

[0006] CN116288252A describes a method for repairing the SiC coating on a graphite disk using MOCVD. Specifically, the graphite disk to be repaired is placed in the reaction chamber of an MOCVD system, and silane and propane gases are introduced to initiate the repair reaction, resulting in a graphite disk with a SiC coating on its surface. However, this method involves re-depositing a SiC coating on the overall outer surface of the graphite substrate, which can affect the overall dimensional accuracy of the substrate.

[0007] CN109841556A uses pure silicon at the damaged SiC coating site, or uses an adhesive to fix pure silicon, allowing silicon to penetrate the damaged area at high temperature and react with carbon paste or graphite to form SiC. However, at high temperatures, molten silicon reacts rapidly with graphite, and the formed SiC hinders further diffusion of silicon and limits the depth of reaction with graphite. For example, the SiC coating formed by the reaction of silicon and graphite in CN109841556A is only 10-30 μm thick, which is lower than the 70-120 μm thick SiC coating obtained on the surface of the graphite disk by CVD. Moreover, pure silicon is difficult to restore the repaired graphite damaged area to the original shape of the intact support disk; in addition, the viscosity of molten silicon is low (Viscosity of molten silicon and the factors affecting measurement. Journal of Crystal Growth 249 (2003) 404–415), and when the repair site is located on the side, sharp point, etc., the molten silicon easily flows outside the repair area. CN109841556A also proposes adding carbon paste, adhesive, and binder in conjunction with pure silicon for repair. The carbon paste consists of a small amount of carbon black and a large amount of resin binder. The carbon paste thermally decomposes at high temperatures, leaving carbon. During repair, pure silicon is adhered to the carbon paste, or pure silicon and binder are combined to form a silica clay that is then applied to the carbon paste. The adhesive and binder vaporize at high temperatures. However, a problem exists: during heat treatment, the large amount of resin (including the binder, binder, and adhesive) decomposes, producing bubbles and cracks. This makes it difficult to form a continuous SiC phase at the repair site after pure silicon welding. When the unreacted residual silicon is removed, bubbles and cracks remain. Furthermore, the adhesive and binder, which temporarily fix the pure silicon, also fail to effectively fix the molten silicon after high-temperature vaporization.

[0008] CN110890309A describes a method that uses machining to create a recessed area on a scrapped graphite disk that covers the damaged area. A graphite repair block, made from graphite blocks, is then used to fill the recessed area. After filling, the block is further processed to conform to the original shape of the scrapped graphite disk, making it an integral part of the disk. Pure silicon solder is then used for hard soldering, bonding the repair block to the disk via capillary penetration. SiC (SiC plating) grows on the surface of the repair block and integrates with the original SiC plating on the disk, completing the repair and allowing the scrapped graphite disk to be reused. However, this method is suitable for relatively flat areas, and it is difficult to achieve a regular structure for curved surfaces. When the pure silicon solder melts into liquid silicon, its low viscosity and tendency to slip prevent sufficient reaction with the graphite repair block surface to grow SiC. This is especially problematic when the repair block surface includes uneven areas or structures such as edges, slopes, curves, protrusions, and pits, where the hard soldering effect is even less ideal. Moreover, the large gap between the graphite repair block and the depression limits the capillary penetration effect, which also restricts the repair effect. Summary of the Invention

[0009] In view of the above-mentioned technical status, the present invention aims to provide a repair method for SiC coating on the surface of graphite base. The method is simple to operate, can obtain a dense SiC repair layer with adjustable thickness, and the repair layer is well bonded to the original SiC coating and graphite substrate. It can be applied to the repair of irregular areas such as arcs and sharp edges, thereby extending the service life of graphite base.

[0010] To achieve the above-mentioned technical objectives, the inventors first used a composite material made of a polymer with high residual carbon content after pyrolysis and silicon carbide filler to fill the damaged SiC coating on the graphite substrate surface. A porous structure was formed by high-temperature carbonization. Then, a slurry formed by elemental silicon and polycarbosilane was melt-infiltrated to transform the polymer and silicon carbide filler filling the repair area into a silicon carbide coating.

[0011] That is, the technical solution provided by the present invention is: a method for repairing the SiC coating on the surface of a graphite substrate, comprising the following steps:

[0012] (1) Fill the damaged area of ​​the SiC coating on the graphite substrate with a composite material made of a polymer with high residual carbon content after pyrolysis and silicon carbide filler; then heat the polymer until it carbonizes to form a porous structure.

[0013] (2) The slurry formed by elemental silicon and polycarbosilane is applied to the porous structure surface after carbonization in step (1), and the slurry is infiltrated at a temperature above the melting point of elemental silicon.

[0014] Damage to the SiC coating on the graphite substrate surface includes, but is not limited to, one or more of the following: cracks, impact points, scratches, breaks, chipping, peeling, corrosion pits, and notches.

[0015] The modification method of the present invention applies whether the SiC coating on the surface of the graphite substrate is damaged, exposing the graphite substrate at the damaged area or not exposing the graphite substrate at the damaged area.

[0016] The filling method is not limited; any composite material formed by the polymer and silicon carbide filler can be used to fill the damaged area, including one or more of brushing, filling, casting, and extrusion. For example, the polymer can be dissolved in a solvent, and then silicon carbide filler can be added and stirred evenly to obtain a thinner slurry. This slurry can then be brushed or dripped onto the damaged area. Alternatively, some of the solvent in the slurry can be removed by distillation or other methods to obtain a thicker slurry, which can then be injected into the damaged area using a syringe. Further methods such as distillation can be used to remove some or all of the solvent to obtain an even thicker slurry, which can then be pressed into the damaged area. The solvent can be selected from those with good solubility in the polymer, preferably solvents with low boiling points to facilitate evaporation and removal.

[0017] The polymers with high residual carbon content after pyrolysis are selected from polymers with a residual carbon content higher than 40 wt% after pyrolysis, including but not limited to polyimide, polyamic acid, polyaryletherketone, phenolic resin, asphalt, and phenolic gel formed by the in-situ reaction of phenolic compounds and formaldehyde. After high-temperature heat treatment, these polymers can remove oxygen-containing groups, nitrogen-containing groups, and H atoms from their structure, leaving behind carbon rich in porous structures.

[0018] The silicon carbide filler includes, but is not limited to, one or more of silicon carbide powder, silicon carbide whiskers, and silicon carbide short fibers. The addition of silicon carbide filler serves two purposes: firstly, it provides skeletal support, preventing the polymer from undergoing thermal deformation, foaming, shrinkage, or even cracking; secondly, it acts as a SiC filler at damaged areas, reducing the polymer content and protecting the damaged areas. If the particle size of the silicon carbide powder is too large, it can lead to surface roughness and uneven carbon distribution in fine repairs. Preferably, the average particle size of the silicon carbide powder is less than 100 μm, and more preferably less than 10 μm. The average length of the silicon carbide whiskers is preferably greater than 50 μm. The average length of the silicon carbide short fibers is preferably less than 1 mm.

[0019] In step (1), the heat treatment temperature can be between 600-1500℃ or even higher. On the one hand, the polymer loses less weight after carbonization, so increasing the temperature would lead to increased energy consumption. On the other hand, if the temperature is too low, the polymer will not be completely carbonized. Therefore, a suitable carbonization temperature is 700-1200℃. To avoid oxidation of the polymer or the carbonized polymer, the heat treatment is preferably carried out in an inert atmosphere or a vacuum environment.

[0020] In the composite of the polymer and silicon carbide filler, the mass ratio of the polymer to the silicon carbide filler is preferably between 1:10 and 5:10. To reduce the residual carbon content, the mass ratio of the polymer to the silicon carbide filler is further preferably between 1:10 and 3:10.

[0021] To reduce foaming or cracking caused by polymer pyrolysis, in addition to optimizing the content of silicon carbide filler, the morphology of silicon carbide filler can also be adjusted. Two types of fillers, silicon carbide powder and silicon carbide whiskers, or two types of fillers, silicon carbide powder and silicon carbide short fibers, or three types of fillers, silicon carbide powder, silicon carbide whiskers and silicon carbide short fibers, can be used.

[0022] To improve the regularity of the repaired material, the carbonized polymer and silicon carbide filler can be polished after step (1).

[0023] The polycarbosilane is a linear or branched polymer compound with a main chain composed of silicon and carbon atoms, and hydrogen or other organic groups attached to the silicon and carbon atoms. It can be converted into SiC ceramics after high-temperature pyrolysis. Polycarbosilane itself or its solution has good fluidity at room temperature, allowing it to penetrate into the porous carbon interstices formed after polymer pyrolysis. When the damaged area exposes the graphite substrate, it can even penetrate to the graphite substrate, thereby improving the adhesion between the repaired area and the graphite. The polycarbosilane solution refers to a solution formed by dissolving or diluting polycarbosilane in a solvent. The solvent is not limited and includes one or more of tetrahydrofuran, hexane, heptane, 2-methyltetrahydrofuran, and toluene.

[0024] The specific chemical formula of the polycarbosilane is not limited. In specific implementation, a liquid polycarbosilane or a polycarbosilane solution that can flow at room temperature is used, and there are no specific requirements for the molecular formula of the polycarbosilane.

[0025] In step (2), polycarbosilane is used in combination with elemental silicon. On the one hand, polycarbosilane can be converted into SiC ceramic after pyrolysis. On the other hand, polycarbosilane can also act as a binder. It not only binds and fixes the porous carbon structure with SiC skeleton formed after the pyrolysis of the polymer and silicon carbide filler, reducing microcracks caused by volume changes during subsequent melting and infiltration, but also binds elemental silicon. Even after the polycarbosilane is pyrolyzed, it will be converted into continuous SiC ceramic, thus avoiding slippage of elemental silicon due to its low viscosity after melting. It is particularly suitable for repairing irregular areas including edges, slopes, arcs, protrusions, pits, sharp points, etc. After the heat treatment temperature is raised above the melting point of elemental silicon, elemental silicon can penetrate into the porous carbon to be repaired through capillary action, converting the porous carbon into SiC and filling the pores, thereby obtaining a dense repair layer.

[0026] In a slurry composed of elemental silicon and polycarbosilane, the preferred mass ratio of elemental silicon to polycarbosilane is between 1:3 and 5:1. Too little elemental silicon results in insufficient reaction of the porous carbon; too much elemental silicon leads to low viscosity at high temperatures, causing it to easily flow to other areas and become difficult to clean. As a further preferred option, the mass ratio of elemental silicon to polycarbosilane is between 2:1 and 4:1.

[0027] To promote melting and infiltration, preferably, in step (2), the melting and infiltration treatment is carried out at a temperature above the melting point of elemental silicon and a gas pressure less than 0.01 MPa. The preferred temperature is 1450-1700℃, and more preferably 1500-1650℃.

[0028] In step (2), polycarbosilane penetrates the porous carbon structure and pyrolyzes to form SiC. Even when graphite is exposed, polycarbosilane can penetrate into the graphite interior and pyrolyze to SiC, thereby improving the bonding strength between the repair layer and the graphite substrate. Compared to polycarbosilane, the viscosity increases after polycarbosilane is combined with silicon to form a slurry, which reduces the penetration rate into the graphite interior. Therefore, as a preferred embodiment, in step (2), when the damaged graphite is exposed, polycarbosilane is first coated onto the surface of the carbonized polymer and silicon carbide filler, and then a slurry formed from silicon and polycarbosilane is coated. The polycarbosilane refers to pure liquid polycarbosilane and / or a polycarbosilane solution. The polycarbosilane solution refers to a solution formed by dissolving or diluting pure polycarbosilane in a solvent. The solvent is not limited and includes one or more of tetrahydrofuran, n-hexane, n-heptane, 2-methyltetrahydrofuran, and toluene.

[0029] The above methods can repair damage of various types and sizes, but when the damage is large, the following solutions can also be adopted:

[0030] (1) A depression that can cover the damaged area is processed at the damaged SiC coating on the graphite substrate surface. According to the size of the depression, a graphite repair block is processed from the graphite block material. The graphite repair block can be inserted into the depression with gaps.

[0031] (2) Coating at least a portion of the inner wall of the depression with a composite material composed of a polymer with high residual carbon content after pyrolysis and silicon carbide filler, and then placing the graphite repair block into the depression; or placing the graphite repair block into the depression, and then filling the gap with a composite material composed of a polymer with high residual carbon content after pyrolysis and silicon carbide filler; or...

[0032] The inner wall of at least a portion of the depression is coated with a composite material composed of a polymer with high residual carbon content after pyrolysis and silicon carbide filler. Then the graphite repair block is placed into the depression, and the gap is filled with the composite material composed of a polymer with high residual carbon content after pyrolysis and silicon carbide filler.

[0033] (3) Heat the graphite substrate treated in step (2) until the polymer is carbonized;

[0034] (4) The slurry formed by elemental silicon and polycarbosilane is applied to the surface of the carbonized polymer and silicon carbide filler, and the melting infiltration treatment is carried out under negative pressure conditions with a temperature above the melting point of elemental silicon and a pressure less than 0.01 MPa.

[0035] To facilitate insertion, the length, width, diameter, and other dimensions of the graphite repair block are smaller than the corresponding dimensions of the recess, thereby forming the gap.

[0036] Preferably, before the graphite repair block is placed into the depression, a SiC coating is deposited on its surface, the thickness of which is consistent with the thickness of the SiC coating on the graphite base surface, thereby reducing the repair area.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention first uses a polymer with high residual carbon content after pyrolysis and silicon carbide filler to fill the damaged area of ​​the SiC coating on the graphite substrate surface. Heating causes the polymer to carbonize and form a porous structure. Due to the supporting effect of silicon carbide, the deformation, foaming or shrinkage of the polymer during the pyrolysis process is greatly reduced, while avoiding the introduction of other impurities. Then, a slurry formed by silicon and polycarbosilane is coated on the surface of the porous structure and heated to above the melting point of silicon. On the one hand, silicon melts into the porous carbon structure and reacts to generate SiC. On the other hand, polycarbosilane melts into the porous carbon structure and pyrolyzes to form SiC. Even when the graphite is exposed, it melts into the interior of the graphite and pyrolyzes to form SiC. Furthermore, due to the presence of polycarbosilane, the melting area of ​​liquid silicon is limited to the vicinity of the porous structure area, avoiding the problem that liquid silicon does not fully participate in the reaction and cannot form a continuous SiC protective layer due to excessive flow caused by low viscosity.

[0039] (2) In this invention, the repair layer formed has no interface with the original SiC coating and has a dense structure. After the repaired graphite substrate is oxidized at high temperature, its mass remains basically unchanged. For example, after oxidizing at 1100℃ for 10-50 hours, the mass change is less than 0.02%, and in some embodiments, the mass change is less than 0.002%.

[0040] (3) In this invention, when the graphite substrate is exposed at the damaged location, the repair material can penetrate into the graphite substrate and form SiC, which greatly improves the bonding force with the graphite substrate.

[0041] (4) In this invention, the repair raw materials and the repair components formed by the reaction are mainly SiC, with few heterogeneous components, which can reduce the influence of the repair area on the epitaxial layer growth atmosphere and help reduce the impact of the repair on the temperature uniformity of the graphite substrate.

[0042] (5) The repair method of the present invention is simple to operate, can repair damaged areas of different locations and sizes, and can obtain a repair structure consistent with the original shape. It has a high success rate and can extend the service life of SiC coated graphite base. Attached Figure Description

[0043] Figure 1 This is the morphology of the polymer after carbonization in Comparative Example 1.

[0044] Figure 2 The image shows the morphology of the carbonized polyamic acid and silicon carbide powder filler in Example 1.

[0045] Figure 3 This is a cross-section of the graphite surface containing a 50μm CVD-SiC coating before and after the SiC coating is formed in Example 2.

[0046] Figure 4 These are scanning electron microscope (SEM) images and energy dispersive spectroscopy (EDS) images of the cross-section of the damaged area of ​​the graphite substrate in Example 3 after repair.

[0047] Figure 5 These are morphological images of the graphite base before and after repair in Example 5. Detailed Implementation

[0048] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the present invention. The accompanying drawings used herein are only for better illustrating the content disclosed in the present invention and do not limit the scope of protection.

[0049] Comparative Example 1:

[0050] Add 5 mL of N,N'-dimethylformamide, 0.31 g of oxyether dianhydride, and 0.2 g of 4,4'-diaminodiphenyl ether to a 100 mL three-necked flask equipped with a mechanical stirrer. Stir at room temperature for 10 h to obtain a relatively viscous polyamic acid solution. Coat the graphite surface with this solution, then place it in an oven and dry at 100 °C for 5 h. Then, increase the temperature to 1200 °C at 3 °C / min and carbonize it for 1 h. Figure 1 The images show the morphology of the polymer after carbonization. The left image is the surface view, and the right image is the internal view. It is visible to the naked eye that the polymer expands significantly in volume after pyrolysis, forming porous carbon with uneven pore size, including pores several millimeters in size. Cracks are generated inside, and the entire polymer detaches from the graphite substrate.

[0051] Example 1:

[0052] To a 100 mL three-necked flask equipped with a mechanical stirrer, add 10 mL of N,N'-dimethylformamide, 0.31 g of oxyether dianhydride, 0.2 g of 4,4'-diaminodiphenyl ether, 1.5 g of SiC powder with an average particle size of 10 μm, and 0.5 g of SiC powder with an average particle size of 5 μm. Stir at room temperature for 10 h to obtain a viscous slurry composed of polyamic acid and silicon carbide powder. Coat the slurry onto a graphite surface, then dry it in an oven at 100 °C for 5 h, and then carbonize it at 1200 °C at a rate of 3 °C / min and hold it for 1 h. Figure 2The left image shows the surface of the carbonized polyamic acid and silicon carbide powder filler, while the right image shows the morphology observed by scanning electron microscopy. It shows that no cracks or bubbles were generated after the polyamic acid and silicon carbide powder filler were carbonized. Even after the surface was polished and the interior was exposed, no cracks or bubbles were found. The scanning electron microscope shows that a porous structure containing SiC particles was formed, which is conducive to the penetration of the slurry formed by silicon powder and polycarbosilane.

[0053] Example 2:

[0054] (1) The polyamic acid and silicon carbide powder composite slurry obtained in Example 1 was coated on the graphite surface with SiC coating. The SiC coating was prepared on the graphite substrate surface by CVD and had a thickness of 50 μm. It was referred to as graphite with 50 μm CVD-SiC coating. Then, it was dried in an oven at 100°C for 5 hours and then heated to 1200°C at 3°C / min and kept at that temperature for 1 hour.

[0055] (2) Add 4g of silicon powder with an average particle size of 5μm and 1g of liquid polycarbosilane (structural formula: {[SiCH2H2]) to the mortar. 0.9 [SiCH2H(CH2CH=CH2)] 0.1} n Mix them evenly to obtain a viscous slurry of silicon powder and polycarbosilane; apply the slurry of silicon powder and polycarbosilane to the surface of polyamic acid and silicon carbide powder filler after carbonization in step (1), and then gradually raise the temperature to 1500℃ under vacuum conditions of 20-50Pa for melting and infiltration treatment, and keep it at 1500℃ for 1 hour.

[0056] Figure 3 Figure (1) shows a cross-section of graphite with a 50 μm CVD-SiC coating before treatment; Figure (2) shows a cross-section of graphite with a 50 μm CVD-SiC coating after treatment using the above steps. It can be seen that the original SiC coating and the newly formed SiC coating are tightly bonded.

[0057] Example 3:

[0058] A graphite substrate with a SiC coating, where the damaged area exposes the graphite substrate.

[0059] (1) The polyamic acid and silicon carbide powder composite slurry obtained in Example 1 was applied to the damaged area, and then dried in an oven at 100°C for 5 hours. The temperature was then increased to 1200°C at 3°C / min and kept at that temperature for 1 hour.

[0060] (2) The slurry formed by silicon powder and polycarbosilane obtained in Example 2 is applied to the surface of polyamic acid and silicon carbide powder filler after carbonization in step (1), and then gradually raised to 1500°C under vacuum conditions of 20-50 Pa for melting and infiltration treatment, and kept at 1500°C for 1 hour.

[0061] Scanning electron microscope image of the repaired damaged area Figure 4 As shown in Figure (1), the energy spectrum analysis is as follows: Figure 4 Figure (2) shows that after repair, dense SiC ceramics are formed at the damaged site, and SiC ceramics are also formed inside the graphite.

[0062] The repaired graphite disk was oxidized in a muffle furnace at 1100℃ for 50 hours, resulting in a weight gain of 0.003 wt%. As a control, pure graphite was oxidized in a muffle furnace at 1100℃ for 10 hours, and the graphite was oxidized into gaseous CO or CO2 and disappeared, indicating that the SiC coating prepared at the damaged area of ​​the SiC coating has high density.

[0063] Example 4:

[0064] The graphite substrate with SiC coating was damaged, exposing the graphite substrate at the damaged area.

[0065] (1) In a 100 mL three-necked flask equipped with a mechanical stirrer, formaldehyde solution with a concentration of 37%-40%, phenol, phenylphenol, and ammonia were added sequentially. The molar ratio of phenol to phenylphenol was 1:1, the molar ratio of aldehyde to phenol was 1.6:1, and the pH was ~10. The reaction solution was heated in a constant temperature water bath to slowly raise the temperature to 80-95℃ and kept at that temperature for 60 min. Then, a vacuum was applied to obtain phenolic resin. 0.6 g of the synthesized phenolic resin was taken and 5 mL of ethanol was added. The mixture was stirred until the phenolic resin dissolved. Then, 1.5 g of SiC powder with an average particle size of 5 μm, 1.0 g of SiC powder with an average particle size of 1 μm, and 0.3 g of SiC whiskers with a length of 10-50 μm and a diameter of 100-500 nm were added and stirred to disperse evenly to obtain an ethanol slurry of phenolic resin and silicon carbide filler. The obtained slurry was applied to the damaged area and kept at 150°C for 120 minutes. Then it was placed in a high-temperature furnace under a nitrogen atmosphere and heated to 1000°C at a rate of 3°C / min. The carbonized phenolic resin and silicon carbide filler formed a porous carbon structure with nanopores.

[0066] (2) Add 3g of silicon powder with an average particle size of 5μm and 1g of liquid polycarbosilane (structural formula: {[SiCH2H2]) to the mortar. 0.9 [SiCH2H(CH2CH=CH2)] 0.1} n Mix 0.5 mL of n-octane with the slurry to obtain a viscous slurry of silicon powder and polycarbosilane. Apply the slurry to the surface of the carbonized phenolic and silicon carbide filler obtained in step (1), and then gradually increase the temperature to 1550°C under a pressure of 10–20 Pa for melt infiltration treatment, and keep at 1550°C for 1 hour.

[0067] Scanning electron microscopy revealed that the SiC coating formed by the repair reaction at the damaged area was dense and tightly bonded to the graphite substrate and the surrounding original SiC coating.

[0068] The repaired graphite substrate was oxidized in a muffle furnace at 1100℃ for 10 hours, resulting in a weight gain of 0.011 wt%.

[0069] Example 5:

[0070] like Figure 5 As shown in Figure (a), the graphite substrate with an 80 μm CVD-SiC coating on its surface is damaged and has a gap, exposing the graphite substrate at the gap.

[0071] (1) Wipe the graphite base clean; take 0.6g of commercially available phenolic resin, add 5mL of ethanol, stir until the phenolic resin dissolves, then add 1.5g of SiC powder with an average particle size of 10μm and 1.5g of SiC powder with an average particle size of 1μm, stir and disperse evenly to obtain an ethanol slurry of phenolic resin and silicon carbide filler; coat the obtained slurry onto the graphite with notches, keep it at 150℃ for 120min, and then place it in a high-temperature furnace under a nitrogen atmosphere to raise it to 900℃ at 3℃ / min.

[0072] (2) The structure of 1g is (SiHCH3CH2). n Solid polycarbosilane is dissolved in n-heptane, and then 3g of millimeter-sized silicon powder is added and stirred evenly to obtain a slurry of polycarbosilane and silicon powder composite. This slurry is coated on the surface of the carbonized phenolic and silicon carbide filler obtained in step (1). The temperature is then gradually increased to 1600℃ under a pressure of 10-30Pa for melt infiltration treatment, and kept at 1600℃ for 1 hour. After cooling, the slurry is removed and the surface is cleaned.

[0073] The repaired graphite base is as follows Figure 5 As shown in Figure (b), the repaired graphite base has a regular and smooth structure with minimal color difference.

[0074] The repaired graphite substrate was oxidized in a muffle furnace at 1100℃ for 50 hours, and the weight gain was 0.002 wt%. No oxidation corrosion was observed at the repair site, indicating that the formed SiC repair coating was dense.

[0075] Example 6:

[0076] A graphite substrate with an 80 μm thick SiC coating was damaged. Part of the graphite at the damaged area was corroded. The damaged area was smaller than a circle with a diameter of 10 mm, and the maximum depth was 4.8 mm. The graphite substrate was repaired as follows:

[0077] (1) A circular hole with a diameter of 10 mm and a depth of 5 mm was processed in the damaged area using a carving machine; a circular piece with a diameter of 9.80 mm and a thickness of 4.8 mm was processed using a carving machine as a modified graphite block using pure graphite as raw material.

[0078] 1.0g of asphalt was heated and dissolved in 10mL of xylene. Insoluble impurities were filtered out using a filter screen. Then, 1.0g of 5μm SiC powder and 3.0g of 40nm SiC powder were added and stirred evenly to obtain an asphalt and SiC powder slurry. This slurry was then applied to the bottom and walls of the processed pit. A repair graphite block was then pressed in, with the height of the graphite block being about 0.1mm lower than the perimeter of the pit. A slurry of asphalt and SiC powder filler was then applied to the top of the graphite block, with a thickness greater than 0.1mm. The graphite base was placed in a high-temperature furnace, and a vacuum was evacuated to replace the high-purity argon gas. The temperature was then increased to 1000℃ at a rate of 2℃ / min and held for 1 hour. After cooling and removal, the surface was polished smooth using sandpaper and polishing cotton. The slurry of polycarbosilane and silicon powder composite from Example 5 was then applied. The temperature was then increased to 1600℃ in a high-temperature furnace at a rate of 2℃ / min and held for 1 hour.

[0079] The repaired graphite substrate was oxidized in a muffle furnace at 1100℃ for 50 hours, and the weight gain was 0.003 wt%. No oxidation corrosion was observed at the repair site, indicating that the SiC formed by the repair was dense and tightly bonded to the surrounding area.

[0080] Example 7:

[0081] A graphite substrate with an 80 μm thick SiC coating was damaged. Part of the graphite at the damaged area was corroded. The damaged area was smaller than a circle with a diameter of 8 mm, and the maximum depth was 3.7 mm. The graphite substrate was repaired as follows:

[0082] (1) A cylindrical pit with a diameter of 8 mm and a depth of 3.7 mm was processed in the damaged area using a carving machine; a circular piece with a diameter of 7.7 mm and a thickness of 3.54 mm was processed using a carving machine as a repair graphite block, and then a SiC coating with a thickness of 80 μm was prepared on the surface of the graphite block by chemical vapor deposition technology.

[0083] The graphite block with the SiC coating deposited was placed in the recess. The asphalt and SiC powder slurry prepared in Example 6 was applied to the gap between the graphite block and the graphite base for repair. After drying, it was placed in a high-temperature furnace, and high-purity argon gas was evacuated and replaced. Then, the temperature was increased to 1000°C at a rate of 2°C / min and held for 1 hour. After cooling, it was removed and coated with the slurry formed by silicon powder and polycarbosilane in Example 2. Then, it was placed in a high-temperature furnace and the temperature was increased to 1650°C at a rate of 2°C / min and held for 1 hour.

[0084] The repaired graphite base was oxidized in a muffle furnace at 1100℃ for 50 hours, and the weight gain was 0.001 wt%. No oxidation corrosion was observed at the repair site, indicating that the SiC repair block formed by the repair is dense and tightly bonded to the surrounding area.

[0085] Example 8:

[0086] A graphite substrate with an 80 μm thick SiC coating was damaged. Part of the graphite at the damaged area was corroded. The damaged area was smaller than a circle with a diameter of 8 mm, and the maximum depth was 3.7 mm. The graphite substrate was repaired as follows:

[0087] (1) A cylindrical pit with a diameter of 8 mm and a depth of 3.7 mm was processed in the damaged area using a carving machine; a circular piece with a diameter of 7.7 mm and a thickness of 3.54 mm was processed using a carving machine as a repair graphite block, and then a SiC coating with a thickness of 80 μm was prepared on the surface of the graphite block by chemical vapor deposition technology.

[0088] (2) Place the graphite block with the SiC coating into the pit. Apply the asphalt and SiC powder slurry prepared in Example 6 to the gap between the graphite block and the graphite base for repair. After drying, place it in a high-temperature furnace, evacuate and replace it with high-purity argon gas, and then raise the temperature to 1000°C at a rate of 2°C / min and hold it for 1 hour. After cooling and taking it out, first apply liquid-phase polycarbosilane for penetration, and then apply the slurry formed by silicon powder and polycarbosilane in Example 2. Then, place it in a high-temperature furnace and raise the temperature to 1650°C at a rate of 2°C / min and hold it for 1 hour.

[0089] The resulting SiC repair block is dense, tightly bonded to the surrounding area, and has a strong bond with the graphite substrate.

[0090] The performance testing in the above embodiments was performed using the following instruments:

[0091] Scanning electron microscope (SEM): Tested using a Hitachi S-4800 field emission scanning electron microscope from Japan.

[0092] Finally, it should be noted that the specific embodiments described herein are merely illustrative of the spirit of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.

Claims

1. A method for repairing SiC coating on the surface of a graphite substrate, characterized in that, Includes the following steps: (1) Fill the damaged area of ​​the SiC coating on the graphite substrate with a composite material composed of a polymer with high residual carbon content after pyrolysis and silicon carbide filler; then heat the composite material until it carbonizes to form a porous structure. The polymer with high residual carbon content after pyrolysis is selected from one or more of polyimide, polyamic acid, polyaryletherketone, phenolic resin, asphalt, and gel formed by in-situ reaction of phenolic compounds with formaldehyde aqueous solution. The mass ratio of the polymer with high residual carbon content after pyrolysis to the silicon carbide filler is between 1:10 and 5:

10. (2) Apply the slurry formed by elemental silicon and polycarbosilane to the surface of the carbonized polymer and silicon carbide filler, and perform melt infiltration treatment at a temperature above the melting point of elemental silicon. After the polycarbosilane is pyrolyzed, it is converted into SiC ceramic. Elemental silicon penetrates into the porous carbon, converting the porous carbon into SiC and filling the pores to obtain a dense repair layer. In the slurry formed by silicon and polycarbosilane, the mass ratio of silicon to polycarbosilane is 1:3-5:

1. After the repaired graphite substrate is oxidized at high temperature (1100℃ for 10-50 hours), the mass change is less than 0.02%.

2. The method for repairing the SiC coating on the graphite substrate surface according to claim 1, characterized in that, Step (1) includes the following steps: (1-1) A depression that can cover the damaged area is processed at the damaged SiC coating on the graphite substrate surface. According to the size of the depression, a graphite repair block is processed from the graphite block material. The graphite repair block can be inserted into the depression with gaps. (1-2) Coating at least a portion of the inner wall of the depression with a composite material composed of a polymer with high residual carbon content after pyrolysis and silicon carbide filler, and then placing the graphite repair block into the depression; or placing the graphite repair block into the depression, and then filling the gap with a composite material composed of a polymer with high residual carbon content after pyrolysis and silicon carbide filler; or, The inner wall of at least a portion of the depression is coated with a composite material composed of a polymer with high residual carbon content after pyrolysis and silicon carbide filler. Then the graphite repair block is placed into the depression, and the gap is filled with the composite material composed of a polymer with high residual carbon content after pyrolysis and silicon carbide filler. (1-3) Heat the graphite substrate treated in step (1-2) until the polymer is carbonized.

3. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 1 or 2, characterized in that, The silicon carbide filler is selected from one or more of silicon carbide powder, silicon carbide whiskers, and silicon carbide short fibers.

4. The method for repairing the SiC coating on the graphite substrate surface according to claim 3, characterized in that, The average particle size of silicon carbide powder is less than 100 μm.

5. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 4, characterized in that, The average particle size of silicon carbide powder is less than 10 μm.

6. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 3, characterized in that, The average length of silicon carbide whiskers is greater than 50 μm.

7. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 3, characterized in that, The average length of silicon carbide short fibers is less than 1 mm.

8. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 3, characterized in that, The silicon carbide filler may be either silicon carbide powder and silicon carbide whiskers, or silicon carbide powder and silicon carbide short fibers, or silicon carbide powder, silicon carbide whiskers, and silicon carbide short fibers.

9. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 1 or 2, characterized in that, The mass ratio of the polymer with high residual carbon content after pyrolysis to the silicon carbide filler is between 1:10 and 5:

10.

10. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 9, characterized in that, The mass ratio of the polymer with high residual carbon content after pyrolysis to the silicon carbide filler is 1:10-3:

10.

11. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 1, characterized in that, In the slurry formed by silicon and polycarbosilane, the mass ratio of silicon to polycarbosilane is 2:1-4:

1.

12. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 1 or 2, characterized in that, In step (2), the melting infiltration process is carried out at a temperature above the melting point of elemental silicon and a gas pressure less than 0.01 MPa.

13. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 12, characterized in that, The temperature is 1450-1700℃.

14. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 13, characterized in that, The temperature is 1500-1650℃.

15. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 2, characterized in that, In step (1-2), before the graphite repair block is placed into the depression, a SiC coating is first deposited on its surface, and its thickness is consistent with the thickness of the SiC coating on the surface of the graphite base.

16. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 1 or 2, characterized in that, When the graphite is exposed at the damaged area, polycarbosilane is first coated on the surface of the carbonized polymer and silicon carbide filler, and then a slurry formed by elemental silicon and polycarbosilane is coated.

17. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 1 or 2, characterized in that, Damage to the SiC coating on the graphite substrate surface includes one or more of the following: cracks, impact points, scratches, breaks, chipping, peeling, and corrosion pits.

18. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 17, characterized in that, The filling method includes one or more of coating, filling, casting, and extrusion.

19. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 1 or 2, characterized in that, The graphite substrate is used to support the substrate on which metal-organic chemical vapor deposition is performed.

20. The method for repairing the SiC coating on the surface of a graphite substrate according to claim 1 or 2, characterized in that, After the repaired graphite substrate is oxidized at high temperature (1100℃ for 10-50 hours), the mass change is less than 0.002%.

Citation Information

Patent Citations

  • Wafer carrier disk maintenance method

    CN109841556A

  • Graphite plate repairing method

    CN110890309A

  • Method for repairing SiC coating on surface of graphite disc by using MOCVD system

    CN116288252A

  • Polycarbosilane and silicon composition and application thereof, SiC ceramic and SiC ceramic-based composite material

    CN116023147A

  • Method for repairing MOCVD graphite tray

    CN116606165A